Prevalence of osteoporosis increased in postmenopausal women with postural scoliosis - Rachmawati, Maria Regina; Sidarta, Nuryani; Bastian, Yefta D. (Universa Medicina, 2012)
BackgroundMenopause is an aging process of the female reproductive system characterized by reduced estrogen levels. This results in increased osteoclastic activity, causing increased bone resorption and thus reduced bone mineral density (BMD). In addition to being influenced by osteoclastic activity, BMD of the lumbar vertebrae is also affected by the erector spinae muscle. The purpose of this study was to determine an association between postural scoliosis and erector spinae muscle endurance and its relation to BMD in postmenopausal women. MethodsThis was a cross-sectional study conducted on postmenopausal women, who were selected by simple random sampling among residents of Mampang Prapatan subdistrict. The postural abnormality of scoliosis was determined by physical examnation, while erector spinae muscle endurance time was assessed using a modified Biering-Sorensen technique, and BMD was measured by bone mineral densitometry, to categorize into normal, osteopenia, and osteoporosis.ResultsA total of 213 postmenopausal women with mean age of 53.52 Â± 3.64 years participated in the study. The prevalence of scoliosis was 54.0%, and osteoporosis was 38.1%. The prevalence of osteoporosis was higher in women with scoliosis (48.7%) in comparison with those without scoliosis (31.6%) (p=0.411). In postmenopausal women with strong erector spinae muscle endurance the risk of of scoliosis was lower (0.76;95% Confidence Interval = 0.58 - 0.99) ConclusionsIn post menopausal women with postural scoliosis found a higher incidence of osteoporosis. High endurance of erector spinae muscle lowers the risk of scoliosis. Exercise to improve posture and increase endurance of erector spinae muscle need to be done to prevent decline of BMD.